2018
DOI: 10.1002/ijc.31980
|View full text |Cite
|
Sign up to set email alerts
|

New use for old drugs: The protective effect of atypical antipsychotics on hepatocellular carcinoma

Abstract: It has been encouraged to use large existing data like insurance claims data to investigate the new indications of old drugs. New strategies of research are warranted to identify feasible drugs. We conducted a dual research model with a population‐based case–control study using Taiwan's National Health Insurance Research Database and an in vitro study to investigate the association between atypical antipsychotic and Hepatocellular carcinoma (HCC) risk. The study herein consists of two components. The first is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The use of different methods to validate the drug's effects on cancer, in addition to using population-based studies, is recommended because of the aforementioned limitation. We observed that some findings from population-based studies cannot be replicated from cell studies, such as the effect of olanzapine on hepatic cell carcinoma [2]. In this study, we extended our previous dual-model study (population-based study and cell study) [2] to a triple-model study (population-based, cell study, and animal study) to detect the cancer-protective effect of specific drugs.…”
Section: Strengths and Limitationsmentioning
confidence: 92%
See 2 more Smart Citations
“…The use of different methods to validate the drug's effects on cancer, in addition to using population-based studies, is recommended because of the aforementioned limitation. We observed that some findings from population-based studies cannot be replicated from cell studies, such as the effect of olanzapine on hepatic cell carcinoma [2]. In this study, we extended our previous dual-model study (population-based study and cell study) [2] to a triple-model study (population-based, cell study, and animal study) to detect the cancer-protective effect of specific drugs.…”
Section: Strengths and Limitationsmentioning
confidence: 92%
“…We observed that some findings from population-based studies cannot be replicated from cell studies, such as the effect of olanzapine on hepatic cell carcinoma [2]. In this study, we extended our previous dual-model study (population-based study and cell study) [2] to a triple-model study (population-based, cell study, and animal study) to detect the cancer-protective effect of specific drugs. The methods provide a research model, and real-world big data may become an essential source of information to discover new possibilities for anticancer drugs.…”
Section: Strengths and Limitationsmentioning
confidence: 92%
See 1 more Smart Citation
“…A new group of 17β‐HSD10 inhibitors are compounds, which are routinely used in clinical practice as drugs for psychiatric disorders. Some atypical antipsychotics were found to have additional effects as anti‐cancer drugs (Chen et al., 2018). The most promising compound is risperidone (18) (Figure 8), an FDA‐approved drug for treating schizophrenia (Marder & Meibach, 1994), which was found to interact with 17β‐HSD10 in a drug screen against the whole genome model of Drosophila melanogaster T7 bacteriophage library (Dilly, Clark, et al., 2017a).…”
Section: Inhibition Of 17β‐hsd10‐aβ Interaction or Enzymatic Activitymentioning
confidence: 99%
“…found quetiapine as the protective agent that reduced HCC risk in patients with schizophrenia. Furthermore, quetiapine also inhibited tumor cell growth and invasion ability in HCC in vitro (4). However, the anti-HCC mechanism of quetiapine has not been elucidated.…”
mentioning
confidence: 96%